Synthesis, Crystal Structure and Vibrational Properties of bis (N-benzylmethylammonium) Pentachlorobismuthate (III) (JOURNAL OF ADVANCES IN CHEMISTRY, 2012)
The [C8H12N]2 BiCl5 compound crystallised in the triclinic system with space group Â P-1 Â with a = 9,833(4), Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â b = 10,044(7), c = 12,225(7) Ã…, a= 78.82(4), Î² = 75,42(4), g= 76.89Â°(5) Â and Z = 2. The average density value, Ïx = 1.518 g.cm-3Â  is in agreement with the calculated one, Ïx = 1.494 g.cm-3. The atomic arrangement can be described as an alternation of organic and inorganic layers. The anionic layer is built up of octahedral [Bi2Cl10]-4. The organic layers are arranged in sandwich between the anionic ones. The crystal packing is governed by means of the ionic Nâ€“H---Cl hydrogen bonds, forming a three dimensional network. The nature of the distortion of the inorganic polyhedra has been studied and can be attributed to the stereo activity of the Bi(III) lone electron pair. The infrared and Raman spectra was recorded in the 4000â€“400 cm-1 frequency region.